Six Simple Rules: How to Manage Complexity without Getting Complicated - Morieux, Yves; Tollman, Peter (Harvard Business Review Press, 2014)
New tools for managing complexityDoes your organization manage complex ity by making things more complicated? If so, you are not alone.Accord ing to The Boston Consulting Group’s fascinating Complexity Index, bus iness complexity has increased sixfold during the past sixty years. An d, all the while, organizational complicatedness—that is, the number o f structures, processes, committees, decision-making forums, and syste ms—has increased by a whopping factor of thirty-five. In their attempt to respond to the increasingly complex performance requirements they face, company leaders have created an organizational labyrinth that ma kes it more and more difficult to improve productivity and to pursue i nnovation. It also disengages and demotivates the workforce.Clearly it ’s time for leaders to stop trying to manage complexity with their tra ditional tools and instead better leverage employees' intelligence. Th is book shows you how and explains the implications for designing and leading organizations.The way to manage complexity, the authors argue, is neither with the hard solutions of another era nor with the soft s olutions—such as team building and feel-good “people initiatives”—that often follow in their wake. Based on social sciences (notably economi cs, game theory, and organizational sociology) and The Boston Consulti ng Group’s work with more than five hundred companies in more than for ty countries and in various industries, authors Yves Morieux and Peter Tollman recommend six simple rules to manage complexity without getti ng complicated.Showing why the rules work and how to put them into pra ctice, Morieux and Tollman give managers a much-needed tool to reinvig orate people in the face of seemingly endless complexity. Included are detailed examples from companies that have achieved a multiplicative effect on performance by using them.It’s time to manage complexity bet ter. Employ these six simple rules to foster autonomy and cooperation and to effectively handle business complexity. As a result, you will i mprove productivity, innovate more, reengage your workforce, and seize opportunities to create competitive advantage.
Keywords: Complexity; Design Thinking